1988
DOI: 10.1021/bi00415a013
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism-based inactivation of horseradish peroxidase by sodium azide. Formation of meso-azidoprotoporphyrin IX

Abstract: Catalytic turnover of sodium azide by horseradish peroxidase, which produces the azidyl radical, results in inactivation of the enzyme with KI = 1.47 mM and kinact = 0.69 min-1. Inactivation of 80% of the enzyme requires approximately 60 equiv each of NaN3 and H2O2. The enzyme is completely inactivated by higher concentrations of these two agents. meso-Azidoheme as well as some residual heme are obtained when the prosthetic group of the partially inactivated enzyme is isolated and characterized. Reconstitution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(106 citation statements)
references
References 23 publications
6
98
1
1
Order By: Relevance
“…ABAH (42) and azide (43) are both inhibitors of MPO, and both attenuated DMPO-MPO adduct formation. Ascorbate is a substrate and also a reductant in that MPO/H 2 O 2 can oxidize ascorbate, but, perhaps more importantly, ascorbate can rapidly reduce many radical intermediates formed by peroxidases (44).…”
Section: Discussionmentioning
confidence: 93%
“…ABAH (42) and azide (43) are both inhibitors of MPO, and both attenuated DMPO-MPO adduct formation. Ascorbate is a substrate and also a reductant in that MPO/H 2 O 2 can oxidize ascorbate, but, perhaps more importantly, ascorbate can rapidly reduce many radical intermediates formed by peroxidases (44).…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have shown that GSH is oxidized to the glutathiyl radical by prostaglandin H synthase and that the glutathiyl radical subsequently attacks the double bond of styrene to form a carbon-centered radical trapped by DMPO (53,78). In addition, the mechanisms for addition of azide and cyanide to the heme of horseradish peroxidase have been proposed to be mediated by azidyl (79) and cyanyl (80) radicals, respectively. In this work, we detected LPO radical-derived DMPO nitrone adducts by both ELISA and Western blotting and the glutathiyl radical by ESR in the interaction of LPO with GSH.…”
Section: Discussionmentioning
confidence: 99%
“…The above pathways involving substrate activation can be advantageous with regard to catalyst deactivation by substrate binding as reported for certain peroxidases. 23 It is noteworthy here that like in the present case, the 1 The kinetic barrier may be associated with the complex nature of the oxo-transfer/oxo-insertion process.…”
Section: Dalton Transactions Papermentioning
confidence: 47%